Analysis of Financial Market Efficiency - Li, Wenyang (International Journal of Global Economics and Management, 2024)
This comprehensive study delves into the intricacies of financial market efficiency, anchored around the Efficient Market Hypothesis (EMH) as postulated by Eugene Fama. It scrutinizes the hypothesis across its weak, semi-strong, and strong forms, incorporating a broad spectrum of empirical evidence and theoretical discourse. In light of recent advancements in technology and the increasing complexity of global financial markets, this paper also explores the impact of high-frequency trading, artificial intelligence, and blockchain technology on market efficiency. Through a meticulous examination of both supportive and critical perspectives on the EMH, the analysis extends to consider the implications of market efficiency on investment strategies, portfolio management, and regulatory frameworks. By juxtaposing traditional financial theories with contemporary market phenomena, this study seeks to offer a nuanced understanding of the dynamic interplay between market efficiency, technological innovation, and investor behavior. The ultimate objective is to provide a balanced viewpoint that acknowledges the merits of the EMH while also recognizing the evolving challenges and opportunities within global financial markets.